Awareness and Knowledge of Ophthalmic Malignancy In Persons Attending Birat Medical College Teaching Hospital - Arjyal Kafle, Prerna; Chaudhary, Neha Priyadarshini; K.C, Ramesh Bikram (Birat Journal of Health Sciences, 2024)
Introduction: Being a vital organ, eye is the most neglected in regard to malignancy. In developing countries, ophthalmic malignancies are often diagnosed at stages when curative treatment is no longer possible and causes high morbidity and mortality. For early diagnosis of ophthalmic malignancies, there should be awareness about it and its risk factors. Objectives: To know about the level of awareness and knowledge of ophthalmic malignancy, its risk factors and to correlate between the literacy status and gender of a person with awareness among people attending ophthalmology outpatient department. Methodology: Random sampling of the people visiting Ophthalmology department were done. Demographic data, awareness about the prevalence of malignancy in any part of the eye and associated risk factors were asked in a prepared proforma. The people were asked about their attitude towards the malignancy and the effect of early screening on prevention of ophthalmic malignancies. Results: Study showed more males and literates, among which 13.57% had more than secondary level education. Only 26.8% were aware of ophthalmic malignancies where 17.46% thought trauma and infections as risk factors. Probable site of malignancy were unknown to 14.28%. Majority agreed, routine eye check-up helps in detecting malignancy and early screening helps in reducing the morbidity and mortality. Conclusion: Awareness in ophthalmic malignancies seems low and is not dependent on the level of education or profession. Awareness among people coming for routine eye examination and conducting screening camps to increase the awareness and knowledge would be beneficial.